An innovative cell-based transplantation therapy for an immature permanent tooth in an adult: a case report - Keyue Liu; Wenxu Li; Sijing Yu; Guimin Li; Ling Ye; Bo Gao (BMC, 2024)
Abstract Background Immature teeth with necrotic pulps present multiple challenges to clinicians. In such cases, regenerative endodontic procedures (REPs) may be a favorable strategy. Cells, biomaterial scaffolds, and signaling molecules are three key elements of REPs. Autologous human dental pulp cells (hDPCs) play an important role in pulp regeneration. In addition, autologous platelet concentrates (APCs) have recently been demonstrated as effective biomaterial scaffolds in regenerative dentistry, whereas the latest generation of APCs-concentrated growth factor (CGF), especially liquid phase CGF (LPCGF)-has rarely been reported in REPs. Case presentation A 31-year-old woman presented to our clinic with the chief complaint of occlusion discomfort in the left mandibular posterior region for the past 5 years. Tooth #35 showed no pulp vitality and had a periodontal lesion, and radiographic examination revealed that the tooth exhibited extensive periapical radiolucency with an immature apex and thin dentin walls. REP was implemented via transplantation of autologous hDPCs with the aid of LPCGF. The periodontal lesion was managed with simultaneous periodontal surgery. After the treatment, the tooth was free of any clinical symptoms and showed positive results in thermal and electric pulp tests at 6- and 12-month follow-ups. At 12-month follow-up, radiographic evidence and three-dimensional models, which were reconstructed using Mimics software based on cone-beam computed tomography, synergistically confirmed bone augmentation and continued root development, indicating complete disappearance of the periapical radiolucency, slight lengthening of the root, evident thickening of the canal walls, and closure of the apex. Conclusion hDPCs combined with LPCGF represents an innovative and effective strategy for cell-based regenerative endodontics.